2008
DOI: 10.1186/1472-6963-8-246
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and implementation of suicide prevention training in one Scottish region

Abstract: Background: As part of a national co-ordinated and multifaceted response to the excess suicide rate, the Choose Life initiative, the Highland Choose Life Group launched an ambitious programme of training for National Health Service (NHS), Council and voluntary organisation staff. In this study of the dissemination and implementation of STORM (Skills-based Training On Risk Management), we set out to explore not only the outcomes of training, but key factors involved in the processes of diffusion, dissemination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
5
22
0
Order By: Relevance
“…This enabled a strong basis for active collaboration and also increased the acceptability of the programme during dissemination (Gendreau, Goggin, & Smith, 1999;Gottfredson & Gottfredson, 2002;Greenberg et al, 2005;Payne, Gottfredson, & Gottfredson, 2006). Similar to earlier studies (Forman et al, 2008;Gask et al, 2008;Gottfredson & Gottfredson, 2002;Greenberg et al, 2005;Kegler, Steckler, Malek, & McLeroy, 1998;Mihalic & Irwin, 2003;Payne et al, 2006), this study showed that support from management is essential to a successful implementation. Although the use of the intervention did not require any major changes to organizations or in work assignments, the tasks related to the programme have not necessarily been taken into account in every municipality.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This enabled a strong basis for active collaboration and also increased the acceptability of the programme during dissemination (Gendreau, Goggin, & Smith, 1999;Gottfredson & Gottfredson, 2002;Greenberg et al, 2005;Payne, Gottfredson, & Gottfredson, 2006). Similar to earlier studies (Forman et al, 2008;Gask et al, 2008;Gottfredson & Gottfredson, 2002;Greenberg et al, 2005;Kegler, Steckler, Malek, & McLeroy, 1998;Mihalic & Irwin, 2003;Payne et al, 2006), this study showed that support from management is essential to a successful implementation. Although the use of the intervention did not require any major changes to organizations or in work assignments, the tasks related to the programme have not necessarily been taken into account in every municipality.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, wider successful dissemination of the programme requires efforts to raise awareness about the importance of prevention of social exclusion and psychosocial ill health among young men, so that decision makers will be willing to allocate resources to prevention activities. Sometimes, it is essential that intervention planners wait for windows of opportunity, when the larger media or policy environment is receptive to the types of change advocated by the intervention (Dearing, 2008;Gask et al, 2008). In this case, there was a lack of evidence-based interventions geared to preventing social exclusion among young men in Finland which greatly enhanced the willingness to implement the Time Out!…”
Section: International Journal Of Mental Health Promotion 105mentioning
confidence: 81%
See 1 more Smart Citation
“…Appleby et al (2000) found significant improvements in suicide risk assessment skills, confidence and attitudes to suicide prevention following Skillsbased Training On Risk Management (STORM®). Further studies showed that all groups of staff regarded STORM highly and thought it relevant to practice (Gask 2008).…”
Section: 'Physician Education'mentioning
confidence: 99%
“…We used evidence gained from phase 2, together with our knowledge of and experience in the diffusion of innovation 377,399,400 to inform implementation strategies at three complementary levels:…”
Section: Introductionmentioning
confidence: 99%